Answer:
(1, -16)
Explanation:
Vertex form of a quadratic equation:
![y=a(x-h)^2+k](https://img.qammunity.org/2023/formulas/mathematics/college/97p0xsjs0cwme4ddvwkim2cbbqprhnlhsv.png)
where:
- (h, k) is the vertex
- a is some constant
Given equation:
![x^2-2x-15=y](https://img.qammunity.org/2023/formulas/mathematics/high-school/nfbys7rvtdqmtn9ozzelmq8cg1borvlp7i.png)
To convert the given quadratic equation to vertex form, complete the square.
Add 15 to both sides:
![\implies x^2-2x-15+15=y+15](https://img.qammunity.org/2023/formulas/mathematics/high-school/wa2bsuvhe5gl2d3drghjzukb8b798ob6eb.png)
![\implies x^2-2x=y+15](https://img.qammunity.org/2023/formulas/mathematics/high-school/nnv36bwm8bdmsmob1k52nnl4bqc335y395.png)
Add the square of half the coefficient of the
term to both sides:
![\implies x^2-2x+\left((-2)/(2)\right)^2=y+15+\left((-2)/(2)\right)^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/syl5lx1fcvl39bv4ji1wzv2d1nwx6au31l.png)
![\implies x^2-2x+1=y+16](https://img.qammunity.org/2023/formulas/mathematics/high-school/wmfkyt8qnt76vlbnqzmpjgv0bz73wr4re4.png)
Factor the left side:
![\implies (x-1)^2=y+16](https://img.qammunity.org/2023/formulas/mathematics/high-school/rknhq7bfcgz3zy0d67acocxqi6733c4zan.png)
Subtract 16 from both sides:
![\implies (x-1)^2-16=y](https://img.qammunity.org/2023/formulas/mathematics/high-school/cf0udqmhj570ysm9oo36j68ny2kj6svk1g.png)
![\implies y=(x-1)^2-16](https://img.qammunity.org/2023/formulas/mathematics/high-school/a76aqt7r4k82fuuzxohq89q3wnq5wze9g0.png)
Comparing with the vertex form:
![\implies h=1, \quad k=-16](https://img.qammunity.org/2023/formulas/mathematics/high-school/h3dksam3f1ewnj6mmkcz9v1azn5j39kurr.png)
Therefore, the vertex of the given quadratic is (1, -16)